Switching to tianeptine in patients with antidepressant-induced sexual dysfunction - Atmaca, M; Kuloglu, M; Tezcan, E; Buyukbayram, A (John Wiley & Sons Ltd, 2003)
Sexual side effects are frequent and are recently being considered as effects of antidepressant treatment. One method to improve the sexual dysfunction associated with the use of antidepressants is to change to another antidepressant. In the present work, the consequences of switching to tianeptine in patients with antidepressant-induced sexual dysfunction were studied. The study group comprised 23 patients with major depressive disorder who experienced antidepressant-induced sexual dysfunction. These antidepressants were stopped and switched to tianeptine (12.5 mg x 3/day). All patients were screened by using the clinical global impression-improvement scale (CGI-I), the Hamilton depression. rating scale (HAM-D) and the Arizona sexual experience scale (ASEX) at the beginning of the study, and at weeks 4 and 8. No patient failed to tolerate 37.5 mg of tianeptine or to complete the study except for one patient becoming pregnant. Paired t-tests revealed a significant difference between baseline and week 4 or week 8 in scores on both the HAM-D and ASEX At 8 weeks, six patients were rated as very much improved (CGI-I = 1) and ten patients were rated as much improved (CGI-I = 2). Thus, with a CGI-I score of 2 or less used to indicate a positive response, 72.7% of the patients were responders. The results suggest that switching to tianeptine appears to be useful for alleviating sexual dysfunction caused by other antidepressants. Copyright (C) 2003 John Wiley Sons, Ltd.
Keywords: tianeptine; sexual dysfunction; SSRI; depression; open-label study